New Study of Stability for New Lorenz-like System - Ahmmed Jumaa; Alaa Hammodat (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, we  studied differential system like of three dimensional Lorenz system. Nonlinear characteristic and basic dynamic properties of three dimensional autonomous system are studied by means of nonlinear dynamics theory, including the stability and we found that the value  is effected by the form of the roots.